Bistatic System Calibration in TanDEM-X to Ensure the Global Digital Elevation Model Quality - Gonzalez, Jaime Hueso; Antony, John Mohan Walter; Bachmann, Markus; Krieger, Gerhard; Zink, Manfred; Schrank, Dirk; Schwerdt, Marco (Isprs Journal of Photogrammetry and Remote Sensing, 2012)
TanDEM-X is an operational satellite mission with the goal of generating a high quality global digital elevation model (DEM) based on synthetic aperture radar (SAR) interferometry in X-band. In order to ensure the quality of the DEM, the differential range measurements and knowledge of the interferometric baseline have to be extremely accurate. In this paper, the bistatic system calibration strategy implemented in TanDEM-X to achieve the desired DEM quality will be described, focusing on the baseline calibration procedure. The results of the most recent tests, which were performed in parallel to the operational DEM acquisition, verify the suitability of this approach.
DLR Import::2019-04-02